What is home? An art-based workshop to explore the physical, relational and wellbeing properties of home - Vallejos, Elvira Perez; Baker, Charley; McGarry, Julie; Joyes, Emma; Carletti, Laura; Bartel, Heike; Jacobs, Rachel; Gale-Feeny, Alice; Higginbottom, Roy (Intellect, 2017)
This feasibility study was framed under the notion of creative practices as mutual recovery – the idea that shared creativity, collective experience and mutual benefit can promote resilience in mental health and well-being. The study evaluated the impact of an art-based workshop designed to examine participant’s notions of home. Thematic analysis was used to evaluate the textual data derived from three focus groups. The findings indicate that art-based workshops that incorporate principles of mindfulness can be used to raise awareness of mental health and well-being issues associated with challenging or inadequate notions of home. These workshops provide a forum for reflection and community in which these problematic notions can be meaningfully articulated and communicated and solutions discussed. This type of creative practice supports the notion of mutual recovery health, helps build resilience among residential workforce and thus helps them to better deal with existing problems.